(untitled) (Nigerian Journal of Technology, 2015)
This paper was aimed at evaluating the functional characteristics of a developed mobility aid for paraplegics in Benin City, Nigeria using their anthropometric data. These functional characteristics were compared with the conventional motorised wheel chair found in most city centres in Nigeria under the same condition. The method adopted in establishing the differences in the developed mobility aid and the conventional types include the use of variables such as, the time required to board, time to complete a 100 meters distance, fuel consumption rate and the subjects’ operational postural angles. The values obtained from these findings were computed and compared with the values obtained from the conventional wheel chair under the same operational conditions. Consequently, the values obtained were subjected to statistical analysis using the Van der Waerden normal score test and the Wilcoxin’s signed rank test. The result of the test showed a remarkable improvement in fuel consumption rate, ease of use and other functional characteristics of the developed mobility aid over the conventional wheelchair available to paraplegics in Nigeria. From the result, it is evidential that the developed mobility aid meets the requirements of adult paraplegics in Nigeria. The use of this mobility aid will make them lead a normal way of life and contribute meaningfully to national growth and development. http://dx.doi.org/10.4314/njt.v35i1.9